Prise en compte des expériences vécues : de la chair des corps à l'intercorporéité dans le monde commun de la vie - Martine Janner Raimondi (Université de Provence, 2020)
Taking into account and reporting on the subject's experiences in biographical research involves a reflection of a phenomenological nature, inspired by Husserl and, in particular, the pragmatic reading established by Depraz (2006), aiming as much to "see" the experience as to "question" the prejudices (Ibid., p. 4). However, access to the phenomena of lived experience cannot be immediate; their accessibility requires an approach that goes beyond the natural attitude developed through the projection of preconceived ideas or pre-established interpretations. The question arises as much on the side of the person directly concerned by a research project as on the side of the researcher with whom he or she is in dialogue, because perceptive, sensitive and imaginative elements inevitably arise, more or less related to memories in connection with the body of flesh of each person and the interactions that take place within it. It is precisely the consideration of the body in relation to the common world of life that is studied in this article in order to demonstrate the interest of a phenomenological approach to lived experience in biographical research, thus opening the way to a hybrid knowledge in which scientific rationality, subjectivity and intersubjectivity are woven.